2020
DOI: 10.37934/cfdl.12.10.6274
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Convection in a Ferrofluid with Internal Heat Generation

Abstract: The nonlinear stability analysis of a ferrofluid layer system is formulated mathematically. This system considered the upper and lower free isothermal boundary with the system heated from below. A mathematical formulation is produced to study the behaviour of the chaotic convection in a ferrofluid layer system using Galerkin truncated expansion. The Boussinesq approximation is opted with the existence of internal heating and the magnetic number. It is found that the transition to chaos in this present study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Analyzed chaos in the industrial field 2020 Senin studied the route to the chaos of a ferrofluid layer system in internal heating [12].…”
Section: Mathematical Model Of An Atmospheric Convective System Consi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzed chaos in the industrial field 2020 Senin studied the route to the chaos of a ferrofluid layer system in internal heating [12].…”
Section: Mathematical Model Of An Atmospheric Convective System Consi...mentioning
confidence: 99%
“…In 2013, Laroze analyzed the chaotic convective behavior of an electrically nonconducting ferrofluid, in contrast to magnetohydrodynamic systems, where chaotic motion is accompanied by appropriate electric currents [11]. In 2020, Senin studied the route to the chaos of a ferrofluid layer system in internal heating [12].…”
Section: Introductionmentioning
confidence: 99%
“…First developed by NASA in the 1960s for space-related applications, ferrofluids have since found a wide array of applications in engineering, medicine, electronics, and various other fields. Some of the notable applications include magnetic sealing, damping, drug delivery systems, loudspeaker technology and cooling in electronics [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding problem in a ferrofluid layer has also been studied 41 . Recently, Senin et al 42 studied the chaotic convection in a ferrofluid layer subject to internal heating and found that the impact of increasing the internal heat source strength is to hasten the instability of the system.…”
Section: Introductionmentioning
confidence: 99%